OPTIMALISASI SEX EDUCATION TERHADAP ANAK BERKEBUTUHAN KHUSUS MELALUI METODE PSIKOEDUKASI MODUSEKSI - Beatrice Mauren Delicia; Nurul Raudatul Auliah; Firdha Apriliana Zahra; Muhammad Adymas Hikal Fikri (PT. Hasba Edukasi Mandiri, 2025)
This study examines the moduseksi psychoeducation method as a means of optimizing sexual education for children with special needs. Sexual education is very important for children with special needs because they are vulnerable to sexual abuse. Therefore, this study aims to provide understanding to children with special needs using the moduseksi psychoeducation method. This study uses a descriptive qualitative approach with a library research method, which is through library research to examine in depth by analyzing various literature sources, so as to obtain a complete and contextually appropriate understanding of the issues of child protection and persons with disabilities. The results of this study show that the moduseksi psychoeducation method is able to increase the understanding of children with special needs regarding sexual education. Thus, moduseksi psychoeducation is effective in increasing sexual education understanding among children with special needs.